Effective subsidies to the demand for fixed broadbandwith an increase in penetration and an undistorted competition landscape: The Colombian case - Jaime Casasbuenas; Fernando de Oliveira; Alexander Riobó (International Telecommunications Society (ITS), 2014)
This article reviews the effectiveness of Colombia's social telecommunications policy in terms of promoting fixed broadband. With a trajectory of almost a decade with subsidies for residential fixed voice, the government changed its policy in the late 1990s moving towards community access for voice and Internet. In 2010, the social telecommunications plan raised the possibility of granting subsidies to fixed broadband to lower income homes throughout the country. Academic research, carried out mainly for the case of the United States, concluded that domiciliary subsidies were not effective and inefficiencies appeared when applied through incumbent operators. The only academic study available for Colombia pointed in the same direction. This work presents an overview of the situation of subsidies for local voice and its evolution towards subsidies for fixed broadband in Colombia. Using a simple econometric exercise, this paper tries to prove that despite the existing evidence against subsidies to the demand, results have been positive in Colombia. This analysis has two main limitations: i) available information is on a quarterly basis; and ii) additional refinements to the econometric model should be introduced to verify the impact of variables such as years of education and degree of urbanization of the population. Facing these constraints, results indicate that subsidies to the demand for fixed broadband applied in Colombia have positively contributed to increase broadband penetration and have not introduced competitive distortions.
Keywords: 330; subsidies; fixed broadband; telecommunications; policy